Drivers of memorable wine tourism experiences – a netnography study - Ilinka Terziyska (Wine Economics and Policy, 2024)
This study serves a dual purpose: firstly, to identify the pivotal architectural components within wine tourism offerings that contribute to a lasting and memorable experience; and secondly, to explore their correlation with the four customer experience realms (4Es). The investigation operates at a micro level, focusing on a specific category of winery – small, family-owned establishments – in an emerging wine destination. Employing a netnography approach, the research design centers on a thematic analysis of visitor reviews sourced from TripAdvisor. The ensuing results are quantified to ascertain the significance of individual factors. A total of 137 reviews spanning the period from June 2013 to May 2022 were manually extracted and coded using MaxQDA. This study’s rationale rests upon two key premises: firstly, the scarcity of research within the specific context of emerging wine destinations from the post-Eastern bloc; and secondly, the limited exploration of the nexus between wine tourism drivers and consumer experiences. The most influential drivers shaping memorable wine tourism encounters that we identified are “people” and “wine”, predominantly associated with the escapist and aesthetic dimensions of experience. These findings diverge markedly from prior research, where the escapist dimension typically received minimal attention. Theoretically, our results enrich understanding by elucidating how the four dimensions of the wine tourist experience intersect with the attributes of the tourism offering, thereby serving as a potential model for future investigations. Moreover, wineries stand to gain valuable insights for product design aimed at enhancing the overall consumer experience.